Defensive Glands of the Darkling Beetle Mesomorphus villiger Blanchard (Coleoptera: Tenebrionidae) - C. M. Seena; Sabu K. Thomas (Psyche: A Journal of Entomology)
Massive home invasion by the darkling beetle Mesomorphus villiger Blanchard 1853 (Coleoptera: Tenebrionidae) during monsoon season make it a nuisance pest in many regions of south India. Morphology of defensive glands and mode of release and dispersal of the defensive secretion were analysed. Defensive glands were separated from the abdominal sternites by cutting along the posterior margin of the seventh sternite. Glands are evaginations of intersegmental membrane between the seventh and eighth sternites consisting of two long sac-like reservoirs, and glandular secretion is released by exudation and spread through epipleural gutter of elytra. Gradual release of the secretion is a strategy to repel the predators for a longer duration.